Diastatotropis elegans (Coleoptera: Anthribidae) from Madagascar: nomenclatural status, redescription and ecological notes - Trýzna, Miloš; Kment, Petr (Zootaxa, 2025)
The nomenclatural status of the species ‘Diastatotropis elegans Fairmaire’ introduced in a key by Frieser (1992) is assessed. The species was never described by Fairmaire, but it was made available by Frieser, who must be accepted as its author. The holotype designated by Frieser (1992) is identified and labelled accordingly. Diastatotropis elegans Frieser, 1992 is redescribed and colour habitus photographs and drawings of male and female genitalia are provided. Ecological notes and photographs of the habitat of this rare species are also added. Based on the available distributional data, D. elegans seems to be endemic to the Montagne d’Ambre massif, northern Madagascar. A checklist of valid species of Diastatotropis Lacordaire, 1865 is provided.